Allocation to Collection Ratio (ACR) pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Sijunjung Tahun 2021 - Widi Nopiardo; Gina Putri (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The problem in this research is that the actual budget for ZIS funds collected and distributed each year is still not fully absorbed or the funds collected are still not distributed and there are also funds distributed that exceed the funds collected. Therefore, by using a measuring tool in the form of ratio analysis, you can see the extent of the Allocation to Collection Ratio (ACR) for the distribution and disbursement of ZIS funds at BAZNAS Sijunjung Regency for the 2021 period. The type of research used is Field Research or field research with an approach quantitative. In 2021 the Gross Allocation to Collection Ratio is 69% with quite effective criteria, Gross Allocation to Collection Ratio Non-Amil is 66% with quite effective criteria, Net Allocation to Collection Ratio is 85% with effective criteria, Net Allocation to Collection Ratio is Non -Amil is 84% with effective criteria, Zakah Allocation Ratio is 90% with very effective criteria, Non-Amil Zakah Allocation Ratio is 89% with effective criteria, Infak and Sadaqah Allocation Ratio is 36% with criteria below expectations, Infak and Sadaqah Allocation Non-Amil Ratio was 22%, below expectations.